1994
DOI: 10.1021/bi00252a011
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Shiga-like Toxin Type 1 B-Subunit with Its Carbohydrate Receptor

Abstract: A study of the binding of the Shiga-like toxin 1 (SLT-1) to the P(k) trisaccharide [methyl 4-O-(4-O-alpha-D-galactopyranosyl)-4-O-beta-D- glucopyranoside] and its constituent dissacharides was carried out. The trisaccharide represents the carbohydrate recognition domain of the neutral glycolipid receptor of the SLT-1, globotriosylceramide (GbOse3). The binding constant for soluble trisaccharide to the soluble pentameric B-subunit is weak, with a K(a) of (0.5-1) x 10(3) M-1 for B-subunit monomer. Scatchard anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(58 citation statements)
references
References 57 publications
4
53
0
Order By: Relevance
“…To avoid complications due to A-subunit interactions, binding studies were performed with purified B-pentamer. Stx1B bound to Gb3 with a K d of about 4 mM (Figure 1A), which is in good agreement with previously published studies using ITC [34] and mass spectrometry [35]. In contrast, no binding of Stx2B to Pk was detected under the experimental conditions tested (Figure 1B).…”
Section: Resultssupporting
confidence: 92%
“…To avoid complications due to A-subunit interactions, binding studies were performed with purified B-pentamer. Stx1B bound to Gb3 with a K d of about 4 mM (Figure 1A), which is in good agreement with previously published studies using ITC [34] and mass spectrometry [35]. In contrast, no binding of Stx2B to Pk was detected under the experimental conditions tested (Figure 1B).…”
Section: Resultssupporting
confidence: 92%
“…Bacterial Shiga-like toxins have a monomeric A subunit bound to a homopentameric B-subunit (Fraser et al, 1994). Whereas the A-subunit contains the enzymatic activity that attacks the 28S RNA of the 60S ribosomal subunit (Endo et al, 1988), the B-subunit interacts with the cellular receptor for the toxin, the glycolipid globotriaosylceramide, and mediates Shiga toxin trafficking (St Hilaire et al, 1994;Johannes et al, 1997;Hagnerelle et al, 2002). Interestingly, studies of Shiga toxin revealed, for the first time, retrograde trafficking from the plasma membrane to the ER (Sandvig et al, 1994), and in addition, exposed a novel endocytic pathway that bypasses late endosomes/prelysosomes en route from the cell surface to the Golgi (Johannes et al, 1997;Mallard et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of Stx1B in complex with the Pk-trisaccharide demonstrates that most of the hydrogen bonding and the stacking interactions occur between the terminal galactose units and the amino acid residues of all three binding sites (40), and binding to glycoconjugates with terminal digalactose (Gal␣1-4Gal) units was observed in previous studies (8). However, in studies using isothermal titration calorimetry (ITC), Stx1 was shown to bind to the Pk-trisaccharide but not to either Gal␣1-4Gal or lactose (31). Since ITC examined binding to the free glycans, the contribution of avidity or the ability to improve binding by engaging multiple binding sites was eliminated and the failure to detect binding to the disaccharide by ITC strongly suggests that all three sugar residues, in the appropriate configuration (␣ or ␤), contribute to binding affinity.…”
Section: Resultsmentioning
confidence: 90%
“…Unlike typical proteincarbohydrate interactions, where a single binding site engages a single glycan, binding of Shiga toxin is the sum of multiple interactions, originating from two distinct mechanisms, protein-glycan interactions at the binding site and avidity, or the ability to enhance binding by simultaneously engaging multiple binding sites on the toxin. For example, Stx1 incubated with a single Pktrisaccharide displays a dissociation constant (K d ) in the millimolar range, and in some studies, binding to Stx2 was 10-fold less avid (31)(32)(33). In contrast, both toxins bind to synthetic Pk glycoclusters (e.g., Starfish and Daisy) (34), linear polymers of Pk-trisaccharide (35), and the silicon-based dendrimers of the trisaccharide (36) in the micro-and nanomolar ranges.…”
mentioning
confidence: 99%